Screening of Potential Vibrio cholerae Bacteriophages for Cholera Therapy: A Comparative Genomic Approach - Barman, Ranjan Kumar; Chakrabarti, Alok Kumar; Dutta, Shanta (Frontiers in Microbiology, 2022)
Cholera continues to be a major burden for developing nations, especially where sanitation, quality of water supply, and hospitalization have remained an issue. Recently, growing antimicrobial-resistant strains of Vibrio cholerae underscores alternative therapeutic strategies for cholera. Bacteriophage therapy is considered one of the best alternatives for antibiotics treatment. For the identification of potential therapeutic phages for cholera, we have introduced a comprehensive comparative analysis of whole-genome sequences of 86 Vibrio cholerae phages. We have witnessed extensive variation in genome size (ranging from 33kbp to 148kbp), GC (G+C) content (varies from 34.5 to 50.8%), and the number of proteins (ranging from 15 to 232). We have identified 9 clusters and 3 singletons using BLASTn and confirmed by nucleotide dot plot and sequence identity. A high degree of sequence and functional similarities in both the genomic and proteomic levels have been observed within the clusters. Evolutionary analysis confirms phages are conserved within the clusters but diverse between the clusters. For each therapeutic phage, the top 2 closest phages have been identified using a system biology approach and proposed as potential therapeutic phages for cholera. This method can be applied for the classification of the newly isolated Vibrio cholerae phage. Furthermore, this systematic approach might be useful as a model for screening potential therapeutic phages for other bacterial diseases.